Flexible Inkjet‐Printed Multielectrode Arrays for Neuromuscular Cartography. Issue 12 (29th April 2016) - Roberts, Timothée; De Graaf, Jozina B.; Nicol, Caroline; Hervé, Thierry; Fiocchi, Michel; Sanaur, Sébastien
Abstract : Flexible Poly(3, 4‐ethylenedioxythiophene)‐poly(styrenesulfonate) (PEDOT:PSS) conductive‐polymer multielectrode arrays (MEAs) are fabricated without etching or aggressive lift‐off processes, only by additive solution processes. Inkjet printing technology has several advantages, such as a customized design and a rapid realization time, adaptability to different patients and to different applications. In particular, inkjet printing technology, as additive and "contactless" technology, can be easily inserted into various technological fabrication steps on different substrates at low cost. In vivo electrochemical impedance spectroscopy measurements show the time stability of such MEAs. An equivalent circuit model is established for such flexible cutaneous MEAs. It is shown that the charge transfer resistance remains the same, even two months after fabrication. Surface electromyography and electrocardiography measurements show that the PEDOT:PSS MEAs record electrophysiological activity signals that are comparable to those obtained with unitary Ag/AgCl commercial electrodes. Additionally, such MEAs offer parallel and simultaneous recordings on multiple locations at high surface density. It also proves its suitability to reconstruct an innervation zone map and opens new perspectives for a better control of amputee's myoelectric prostheses. The employment of additive technologies such as inkjet printing suggests that the integration of multifunctional sensors can improve the performances of ultraflexible brain‐computer interfaces. Abstract : Inkjet printed flexible PEDOT:PSS multielectrode arrays (MEAs) mapping the neuromuscular activity of an upper arm are reported. The device is validated by Electrochemical Impedance Spectroscopy, electrocardiographic and electromyographic recordings. Such results provide a new opportunity to control the movement of prosthesis with such MEAs.